Membangun Loyalitas dan Kinerja Karyawan Melalui Kompensasi, Lingkungan Kerja dan Budaya Organisasi (Studi pada Karyawan UNDHA AUB Surakarta) - BRM Suryo Triono; Jarot Santosa; Suparni Suparni (ProBank, 2025)
The purpose of this study was to examine the development of employee loyalty and performance through compensation, work environment, and organizational culture. The t-test results showed that organizational culture had a positive and significant effect on employee loyalty, compensation had a positive but insignificant effect on employee loyalty, and work environment had a negative but insignificant effect on employee loyalty. Organizational culture had a positive and significant effect on performance, while compensation and work environment had a positive but insignificant effect on performance, and employee loyalty had a negative and insignificant effect on performance. The total R2-square value was 0.5141, indicating that employee performance variables were explained by compensation, work environment, and organizational culture, with work loyalty as the intervening variable at 51.41% and the remaining 48.59% explained by other factors outside the research model. The most effective and dominant variable in improving employee performance at UNDHA AUB Surakarta was organizational culture.